Distinct functional elements for outer-surface anti-interference and inner-wall ion gating of nanochannels - Pengcheng Gao (Nature Portfolio, 2018)
Nanochannels are often modified with functional elements, but most studies have focused on functionalizing only the inner wall. Here, the authors design nanochannels with distinct chemical modifications on the inner and outer surfaces, providing a route to dual-function channels.